2019
DOI: 10.1111/1753-0407.12890
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of sodium glucose co‐transporter 2 inhibitors combined with insulin in adults with type 1 diabetes: A meta‐analysis of randomized controlled trials

Abstract: Background The safety and efficacy of sodium glucose co‐transporter 2 (SGLT2) inhibitors in a dose‐dependent manner for type 1 diabetes mellitus (T1DM) are unclear. Methods Randomized clinical trials (RCT) were searched from PubMed, EMBASE, the Cochrane Library, Web of Science and ClinicalTrials until August 2018. Results Thirteen RCT with 5397 participants were included. SGLT2 inhibitors were proved to be effective in glycemic control and weight loss in T1DM. In the subgroups of different doses, SGLT2 inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
(66 reference statements)
2
28
0
Order By: Relevance
“…Three meta‐analyses assessing the efficacy and safety of SGLT2 inhibitors in T1D were recently published . One report included four RCTs with 485 participants and found no significant difference in the rate of adverse events .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three meta‐analyses assessing the efficacy and safety of SGLT2 inhibitors in T1D were recently published . One report included four RCTs with 485 participants and found no significant difference in the rate of adverse events .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to baseline HbA1c, it is theoretically possible that the risk of DKA was higher in those with higher HbA1c levels, 31 Three meta-analyses assessing the efficacy and safety of SGLT2 inhibitors in T1D were recently published. [21][22][23] One report included four RCTs with 485 participants and found no significant difference in the rate of adverse events. 21 One report included 14 RCTs with 4591 participants 22 : four included RCTs were of short duration (less than 12 weeks) with a relatively small sample size 5,7,32,33 and four were conference abstracts with incomplete outcomes.…”
Section: Figurementioning
confidence: 99%
“…They reported that SGLT-2 inhibitors in comparison to GLP-1 receptor agonists were not associated risk of serious UTIs. 19 Liu J et al, in their systemic review and meta-analysis of randomized controlled trials on the effects of SGLT-2 inhibitors on UTI and genital infections demonstrated no significant difference between SGLT-2 inhibitor group and control. 20 The reported incidence of genital infections was again highest amongst the users of dapagliflozin (76.92%) followed by empagliflozin and canagliflozin.…”
Section: Discussionmentioning
confidence: 98%
“…The results were in line with meta-analysis of randomized controlled trials (RCTs) on SGLT-2 inhibitors safety and efficacy by Liu XY et al The metaanalysis clearly highlighted the increased risk of UTIs in users of SGLT-2 inhibitors in comparison to placebo. 19 However; this was refuted by Ueda P et al, in their nationwide registry based cohort study assessing the use of SGLT-2 inhibitors and risk of serious adverse events. They reported that SGLT-2 inhibitors in comparison to GLP-1 receptor agonists were not associated risk of serious UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…The articles written by Dandona 2017 and Dandona 2018 were about the same study but differed in the follow-up duration other hand, many studies of combined treatment of type 1 diabetes with SGLT-2 inhibitors and insulin have shown that SGLT-2 inhibitors effectively control blood sugar levels, reduce insulin demand, and promote weight loss. However, potential side effects, such as diabetic ketoacidosis and infection, have attracted widespread scrutiny [11][12][13][14]. So far, the U.S. Food and Drug Administration (FDA) and the European Medicines Agency (EMA) have approved four SGLT2 inhibitors (canagliflozin, dapagliflozin, empagliflozin, and ertugliflozin).…”
Section: Literature Retrieval and Study Selectionmentioning
confidence: 99%